Help-seeking behavior in bereaved university and college students: Associations with grief, mental health distress, and personal growth - Tureluren, Emilie; Claes, Laurence; Andriessen, Karl (Frontiers in Psychology, 2022)
Many students have experienced the death of a loved one, which increases their risk of grief and mental health problems. Formal and social support can contribute to better coping skills and personal growth in bereaved students. The purpose of this study was to examine the support that students received or wanted to receive and its relation to students’ mental health. We also looked at students’ needs when receiving support and barriers in seeking formal and social support. Participants (N = 666) completed an online survey consisting of questions about their sociodemographic characteristics, the support they received or wanted to receive, and support needs and barriers in seeking support. The survey also included three scales assessing grief, mental health distress and personal growth. First, we analyzed the data descriptively. Next, we used MANCOVA to examine whether students who did or did not receive or wanted more support differed in terms of their grief, mental health distress or personal growth. About 30% of students needed more support and experienced more grief and mental health distress than students who had their support needs met. Students who received support experienced more personal growth and grief than students who did not receive support. Students indicated a need for feeling acknowledged and safe. Feeling like a burden to others and perceiving their problems as not serious enough to warrant support were common barriers to seeking support. Our results indicate that support should be provided actively to students after the death of a loved one, and support being available on an ongoing basis.